Russia’s Economic Position in the Post-Soviet Union Space: the Evolution Between 2000-2019 - TĂTAR, Andrei Viorel (Presa Universitară Clujeană, 2024)
The main motivation of this thesis is comprised in the change of paradigm, from geopolitics to geoeconomics enforcing the “soft power” terminology. Alongside the ideological motivation is the re-emergence of Russian Federation on the international stage. This re-emergence is scarcely analyzed and presented in literature, and even more, it is rarely linked to geo-economic factors. This process developed in time, and the academic analysis failed to cover this subject because of other urgent issues like the economic crisis, migrant crisis and the wars in the Middle East. It is interesting how the “Russian bear” has awakened after the Ukrainian Conflict and Russia combines military (“hard power”) with economics (“soft power”). This things mostly happened because of the Russian need of counterbalancing the economic power of the western bloc, here in name of European Union and its close partners.